Reversible C═N Bond Formation Controls Charge-Separation in an Aza-Diarylethene Photoswitch - Sacherer, Maximilian-Tobias; Gracheva, Sofia; Maid, Harald; Placht, Christian; Hampel, Frank; Dube, Henry (Journal of the American Chemical Society, 2024)
Diarylethenes belong to the most eminent photoswitches and have been studied for many decades. They are found in virtually every field of application and have become highly valuable molecular tools for instilling light-responsiveness into materials, catalysts, biological systems, or pharmacology. In this work, we present a novel and distinct type of pyrimidine-based aza-diarylethene, which undergoes a highly unusual zwitterion-forming photoreaction. During this fully reversible process, a CN double bond is established under concomitant aromatization and thiophene-ring opening. The metastable zwitterion thus possesses a positively charged extended aromatic structure and an independent conjugated thiolate function. It can further photoisomerize between a more stable Z and a less stable E isomer, resulting in effective four-state photoswitching. Unusual for diarylethenes, the metastable isomers show negative solvatochromism and red-shifted absorption in apolar solvents. With this behavior, aza-diarylethenes effectively bridge the properties of merocyanines and diarylethenes. Thermal stability of the zwitterions can be modulated from very labile to highly stable behavior in response to pH, again in a fully reversible manner. Pyrimidine-based aza-diarylethene thus establishes a unique photoreaction mechanism for diarylethenes, allowing control of charge separation, thermal stability, and color generation in a different way than hitherto possible.
CRIS-Team Scopus Importer:2024-04-26